Cultural Narratives in Proverbs: A Sociocultural Perspective on Transmission and Adaptation - Jannat Kashif; Manahil Asif; Tooba Ijaz (Dialogue Social Science Review (DSSR), 2025)
Proverbs are concise expressions of cultural wisdom, symbolizing societal values and moral lessons that have been transmitted across generations. This study examines the role of proverbs as tools for cultural preservation and moral guidance through the lens of Vygotsky’s Sociocultural Theory. The findings reveal that proverbs, introduced in communal settings, are internalized through social interactions, where guidance from more knowledgeable individuals fosters the development of reasoning, decision-making, and moral evaluation. By transforming from shared cultural expressions into personal cognitive tools, proverbs bridge collective heritage and individual thought. Their adaptability ensures their significance in current contexts, providing pragmatic frameworks for progressing through modern ethical and social challenges. This research highlights the dual role of proverbs in shaping individual cognition and maintaining cultural identity, as well as contributing to their continuing significance. The study concludes by emphasizing the need to explore how proverbs evolve in response to globalization and digital communication, ensuring their continued impact in diverse and changing societies.